What is a nematode? - Zullini, Aldo (Zootaxa, 2012)
In their classic book “An Introduction to Nematology” Chitwood & Chitwood (1950) wrote (1): “Having briefly considered the history of general nematology, the question naturally arises, “What is a nematode?”. In answering this question it is necessary first to designate a nematode as a triploblastic, bilaterally symmetric, unsegmented, non-coelomate animal of the Series Scolecida Huxley, 1865”. Actually, definition of taxa is not an easy task, because monothetic characters are rare, as polythetic traits are more common and evident, albeit of probabilistic value. To highlight this problem, the following paradoxical but empirically correct diagnosis of the taxon Nematoda is given.